Recovery Gaps for Child Victims of Intrafamilial Sexual Violence by Family Member in Indonesia’s Criminal Justice System - Shelly Adisti Setiawati; R. Rahaditya (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Sexual violence against children committed by family members constitutes a serious criminal offense that generates long-term physical, psychological, and social consequences for child victims within unequal family power relations. Specific Background: Indonesian legal instruments, particularly Law Number 35 of 2014 concerning Child Protection and Law Number 12 of 2022 concerning Sexual Violence Crimes, formally regulate special protection, victim recovery, restitution, and integrated legal safeguards for child victims of intrafamilial sexual violence. Knowledge Gap: Despite the existence of comprehensive legal provisions, judicial implementation remains predominantly centered on perpetrator punishment, while victim-oriented recovery mechanisms and restitution are insufficiently integrated into court practices. Aims: This study aims to analyze the regulatory framework and the fulfillment of legal protection and victim rights for child victims of sexual violence perpetrated by family members within Indonesia’s criminal justice system. Results: Using normative legal research through statutory and case approaches, particularly the analysis of Medan District Court Decision Number 1665/Pid.Sus/2024/PN Mdn, the study finds that Indonesian positive law comprehensively recognizes children’s rights to handling, protection, recovery, rehabilitation, and restitution. However, the implementation of these rights remains suboptimal due to limited integration of psychological recovery, social rehabilitation, and victim-centered protection mechanisms in judicial practice. Novelty: This study highlights the persistent disparity between normative victim protection provisions and their practical application in intrafamilial sexual violence cases involving children. Implications: Strengthening integrated handling mechanisms, inter-agency coordination, trauma-informed legal processes, and the best interests of the child principle is essential to prevent revictimization and improve child victim recovery within Indonesia’s criminal justice system. Highlights: Indonesian positive law recognizes comprehensive safeguards for minors experiencing sexual abuse within family environments. Judicial practice prioritizes offender sentencing over psychosocial rehabilitation and restitution mechanisms. Integrated coordination among legal institutions remains necessary to prevent repeated victimization of children. Keywords: Child Victims, Sexual Violence, Family, Legal Protection